(Re)Discovering Self Women's Construction of Identities: Socio-cultural View - E. V. Swai (Adult Education Research Conference, 2006)
Through an analysis of how women participate in constructing their identities, this paper interrogates the notions of construction of identity (womanhood identity) as a learning activity among women in Lukani Tanzania. Current dominant theoretical framework in adult education and feminist literature have typically positioned African women as “unknowers” and marginalized in the process of knowledge construction and learning-a link thoroughly constructed both by positivists and poststructural theorists who have called attention to African women’s limitation in participating in learning and development.
Keywords: Womanhood identity; African women; learning identity